Thirsty for gold! Slaking the diggings from California to Bendigo. Issue 5 (1st May 2013) - Russell, Geoff
Abstract : Nineteenth century gold rushes in California and Australia spurred a frenzied scramble to secure ample year‐round supplies of water for gold washing and for sustaining life in primitive frontier mining settlements teeming with diggers struck with "gold fever."